Metode Pelaksanaan Pekerjaan Beton Bertulang Pada Proyek Pembangunan Creative Center Majalengka - Nurhasanah, Rita; Rijaluddin, Arief; Susandi, Dony (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
The implementation of a building construction project consists of several stages of work that must be passed. Implementation of structural work requires methods that can be carried out effectively and efficiently. This study aims to determine the method of carrying out reinforced concrete structure work for columns, beams, and floor plates in the Majalengka Creative Center Building project. The results of the study are that the implementation method carried out on column, beam and floor plate work on the Majalengka Creative Center building project is in accordance with the planning and refers to the RKS (Work Plan and Requirements) for structural work. The process of carrying out reinforced concrete structure work for columns, beams, and floor slabs briefly includes preparatory work, formwork work, ironing work, casting, and curing of concrete structures.